2011
DOI: 10.3892/ijo.2011.956
|View full text |Cite
|
Sign up to set email alerts
|

PLU-1/JARID1B/KDM5B is required for embryonic survival and contributes to cell proliferation in the mammary gland and in ER+ breast cancer cells

Abstract: Abstract. The four members of the JARID1/KDM5 family of proteins, a sub-group of the larger ARID (AT rich DNA binding domain) family, have been shown to demethylate trimethylated lysine 4 on histone 3 (H3K4me3), a chromatin mark associated with actively transcribed genes. In some lower organisms a single homologue of JARID1 is found, and functions of the four proteins found in mice and humans may be specific or overlapping. To investigate the function of the JARID1B protein we examined the effects of deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 0 publications
5
76
2
Order By: Relevance
“…Complete and functional JARID1B knock-out mice have defects in pubertal mammary gland development, including a reduced number of TEBs, less side branching, and impaired ductal elongation [57, 58]. JARID1B mRNA is expressed in both murine basal and luminal lineages (Holliday et al, unpublished data) and seems to be important for rapid epithelial cell proliferation during puberty but not in alveolar development during pregnancy since JARID1B knock-out mice are able to produce milk [58].…”
Section: Histone Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete and functional JARID1B knock-out mice have defects in pubertal mammary gland development, including a reduced number of TEBs, less side branching, and impaired ductal elongation [57, 58]. JARID1B mRNA is expressed in both murine basal and luminal lineages (Holliday et al, unpublished data) and seems to be important for rapid epithelial cell proliferation during puberty but not in alveolar development during pregnancy since JARID1B knock-out mice are able to produce milk [58].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Zou et al [58] observed co-binding of JARID1B and the luminal transcription factor GATA3 at the Foxa1 and Stat5a promoters and loss of GATA3 binding in JARID1B knock-out mammary epithelial cells, arguing that JARID1B and GATA3 can act co-operatively to mediate transcription. JARID1B has also been shown to interact with oestrogen receptor (ER)α in the COS-7 cell line [57]. However, this has not been validated in mammary epithelial cells.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Knockdown of KDM5B in mESCs resulted in failure to differentiate to neurons, whereas knockout in mouse neural stem cells (mNSCs) revealed that loss of KDM5B at this later stage does not affect differentiation to mature neurons [91,92]. Knockout of KDM5B in mouse is embryonic lethal [93], and, remarkably, overexpression also leads to impaired neural differentiation [90]. This suggests tight control of this demethylase is critical for cell fate determination.…”
Section: Kdm5b Mutations In Id and Asdmentioning
confidence: 99%
“…PLU-1 is frequently overexpressed in breast cancer and downregulation of PLU-1 impairs breast cancer growth in vivo (Barrett et al 2002; Catchpole et al 2011). Similarly, PLU-1 is overexpressed in bladder and lung cancer where its inhibition leads to apoptosis (Hayami et al 2010).…”
Section: -Oxoglutarate-dependent Dioxygenases As Cancer Therapeutic mentioning
confidence: 99%